Accounting for shifting distributions and changing productivity in the development of scientific advice for fishery management. (17th April 2019) - Karp, Melissa A; Peterson, Jay O; Lynch, Patrick D; Griffis, Roger B; Adams, Charles F; Arnold, William S; Barnett, Lewis A K; deReynier, Yvonne; DiCosimo, Jane; Fenske, Kari H; Gaichas, Sarah K; Hollowed, Anne; et al.
Abstract: In the United States, implementation of strong legislative mandates and investments in scientific programmes have supported sustainable fisheries management for seafood production, marine ecosystems, and maritime communities and economies. Changing climate and ocean conditions present new and growing challenges that affect the ability to manage fisheries. To better prepare for and respond to these challenges, the U.S. National Marine Fisheries Service has called for increasing the production, delivery, and use of climate and environmental information to fulfil its living marine resource stewardship mandates. Addressing these challenges and more formally including climate-informed decision-making in the fisheries management process requires strengthening and adapting the current fisheries management framework. We focus on two impacts of a changing climate, shifting species distributions and changing productivity, which can have significant implications for effective fisheries management. We identify six key steps of a climate-informed science-to-management system: detecting changes, understanding mechanisms of changes, evaluating risks and priorities, conducting assessments, communicating advice, and making management decisions. For each step, we identify challenges and provide recommendations to address those challenges and increase the capacity to develop and apply climate-related science to support sustainable fisheries management in a changing world.